2017
DOI: 10.5267/j.esm.2017.9.002
|View full text |Cite
|
Sign up to set email alerts
|

A review of the fatigue strength of structural materials under multiaxial loading in terms of the local energy density

Abstract: A review of some recent data from multiaxial fatigue data from different notched materials is carried out in the paper. The approach based on the strain energy density (SED) averaged over a control volume is first used to summarise uniaxial and multiaxial fatigue strength data of welded joints made of structural steel and aluminium alloys. In all welded joints, the weld toe and weld root regions are modelled like sharp, zero radius, V-notches with different opening angles. The control volume radius is 0.28 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Single-edge notched beam (SENB) test [16][17][18], double-edged notched tension (DENT) test [19], disk shaped compact tension (DCT) test [20][21][22], Edge notched disc bend (ENDB) test [23][24][25][26][27], and semicircular bend (SCB) test [28][29][30][31][32][33][34][35][36][37], are to name a few. Disc-shaped compact tension (ASTM D7313-07a) and semicircular bending (SCB) tests [29,[38][39][40][41][42] are among the frequently used fracture specimens for evaluating fracture behavior of asphalt concretes. Cylindrical samples obtained from Superpave Gyratory Compactor (SGC) or cores achieved from field and underservice AC layers can be used to build SCB samples which is known as low-cost test.…”
Section: Introductionmentioning
confidence: 99%
“…Single-edge notched beam (SENB) test [16][17][18], double-edged notched tension (DENT) test [19], disk shaped compact tension (DCT) test [20][21][22], Edge notched disc bend (ENDB) test [23][24][25][26][27], and semicircular bend (SCB) test [28][29][30][31][32][33][34][35][36][37], are to name a few. Disc-shaped compact tension (ASTM D7313-07a) and semicircular bending (SCB) tests [29,[38][39][40][41][42] are among the frequently used fracture specimens for evaluating fracture behavior of asphalt concretes. Cylindrical samples obtained from Superpave Gyratory Compactor (SGC) or cores achieved from field and underservice AC layers can be used to build SCB samples which is known as low-cost test.…”
Section: Introductionmentioning
confidence: 99%
“…Torbani [10] investigated the damage of an O, U, V-shaped slotted plate where he used the point stress criterion combined with the equivalent material concept, he concluded that the accuracy of each failure criterion depends on essentially the characteristic of the notch and therefore the distribution of stresses around the edge of the notch. Other researchers such as berto and all [11] have worked on uniaxial and multiaxial fatigue for different types of notches. The approach is based on strain energy density (SED) of a steel and aluminum alloys structure to tension, torsion and combined tension and torsion.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of significant progress in the study of the effect of welding residual stress on the fatigue crack growth rate, the interpretation of most results is given in terms of the stress intensity factor in the framework of the validity of linear elastic fracture mechanics. It should be noted that other failure theories such strain‐based criteria can also be used to predict the fatigue life of welded structures …”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that other failure theories such strain-based criteria can also be used to predict the fatigue life of welded structures. [15][16][17][18][19][20][21][22] The nonsingular (T-stress) term in the Williams series expansion 23 characterizes the crack-tip constraint and plays significant role in linear elastic fracture mechanics having influence on the crack-tip plastic zone, the fracture toughness, crack paths, and the fatigue crack growth rate (eg, previous studies [24][25][26][27][28][29][30][31][32] ). Seitl and Knesl 32 have introduced the T-stress in the Paris-Erdogan law to reflect the effect of crack-tip constraint on the fatigue crack propagation rate.…”
mentioning
confidence: 99%